PERSENTASE KARKAS DAN POTONGAN KOMERSIAL ITIK LOKAL JANTAN YANG DIBERI LARUTAN BUNGA KECOMBRANG DALAM PAKAN - Komara, Fatutthorman; nur, Hanafi; Handarini, Ristika (Universitas Djuanda Bogor, 2018)
Torch ginger flower which functions as antibiotic and antioxidant is potential to be used as feed additive in ration to improve local duck production. This study was aimed at assessing the effects of the inclusion of torch ginger flower solution in rations on the percentages of carcass and meat commercial cuts of male local ducks. The study was conducted at Poultry Laboratory of Department of Animal Husbandry, Faculty of Agriculture, Djuanda University, Bogor from June to August 2016. Twenty-four male local ducks aged 2 weeks with mean initial body weight of 450±70.35 g were used. Ducks were fed basal rations containing 20–22% crude protein. Torch ginger flower solution was included in the rations. Ducks were allocated into battery cages of 150 x 40 cm each. A completely randomized design with 4 treatments and 3 replicates was used. Treatments consisted of commercial ration (PK) + 0% torch ginger flower solution (LBK) (R1), PK + 2.5% LBK (R2), PK + 5% LBK (R3), and PK + 7.5% LBK (R4). Measurements were taken on the percentage of carcass and meat commercial cuts (wing, breast, back, thigh). Data were subjected to an analysis of variance and a Duncan test. Results showed that treatments gave significant effects (P<0.05) on carcass percentage but not on meat commercial cuts. It was concluded that the inclusion of torch ginger flower solution in rations of up to 7.5% increased carcass percentage and tended to increase breast and thigh percentages. It was suggested that the inclusion of torch ginger flower solution in rations be done by 5% to result in higher and more economical duck meat commercial cuts (breast and thigh). Key words: carcass percentage, commercial cuts, male local duck, torch ginger flower solution